THE REVIEW OF MASLAHAH MURSALAH ON THE E-COURT SYSTEM AT RELIGIOUS COURT - Siti Inayah; Hilda (Universitas Islam Indonesia, 2023)
As a result of the industrial revolution, technological developments in the world are increasingly massive. Almost all systems of human life are assisted by sophisticated technologies and are connected to the internet. This aims to facilitate human work and activities, including government services which currently have many collaborated with sophisticated technology in maximizing public services. This step is seen as the right step, considering the sophistication of existing technology that is considered more effective and efficient in carrying out public services. As for Islam, the technological progress that enters almost all aspects of human life is seen as a form of maslahah mursalah, which is something that is permissible by syara' as long as it is good acording to the reason and can provide good also avoid bad things for humans. One of the government institutions that uses technology in providing services to the public is the religious court, as a legal instrument where the community can seek justice according to the culprit it handles, a religious court of course must provide maximum service to the community. Through Supreme Court Regulation No. 1 of 2019, the government provides a new innovation by implementing an electronic court system (E-Court) which aims to make it easier for people to litigate. The obstacles that were previously encountered when people were in litigation such as distance, time, and expensive costs were expected to be overcome by the existence of an E-Court which aims to realize fast and cost-effective administration in order to achieve the ideals of an efficient and effective court. For this reason, this research is deemed necessary to see whether these goals have been achieved or not and whether they are in accordance with the mursalah maslahah. This research is a qualitative research with in-depth interview approach and literature study.